Effect of pharmacovigilance training programme on quantitative and qualitative adverse drug reaction reporting - Jogdand, Sangita D.; Padhye, Mugdha R.; Nagpure, Shailesh; Shinde, Raju K. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Adverse Drug Reactions(ADRs) are required to monitored in post marketing phase for unstudied ADR or beneficial effect which were not evident in controlled study design, but ADRs are usually under reported due to misbelieves or ignorance of health care worker. There is increasing numbers of adverse drug reaction monitoring centers in India affiliated to governing council but are in primitive phase. Also, there is lack of knowledge and attitude towards necessity for proper reporting of ADR, understanding of terminologies. Hence present study was undertaken to assess out of educational intervention in the form of simulated ADR workshop. Methods: Hundred nursing staff of JNMC were trained through Simulation Workshop i.e. initial knowledge as assessed before intervention, followed by explanations of every terminology essential for quality reporting of ADR. Ideal ADR reports were provided for study and ADR scenario was given for reporting of ADR. Deficiencies in reported ADR explained to participants. Post intervention knowledge and reporting was assessed. Deficiencies in actual ADR were pursued for three months. Results: There was statistically significant improvement observed in knowledge (p <0.01) and corresponding, proportionate quality parameters of ADRs as suggested by Z test. Conclusions: Educational intervention through simulated ADR and understanding about significance of ADR reporting’s and related terminologies improves quality as well as numbers of ADR reporting.